Şia'da Cifr İlminin Yeri - Mehmet Atalan (Dini Araştırmalar, 2015)
According to the Shia, al-Jafr is a book which Alî b. Abi Talib inherited from the Prophet. It contains knowledge of past and future events. “Jafr” means a “four month-old lamb”. When referenced in scientific terminology, the word “Jafr” relates to a branch of predicting future events beforehand. According to Shia, there are two types of Jafr - the white and red jafr. The white (abyaz) jafr contains the previous scriptures e.g. the psalms, Torah and Injil and even the scrolls (suhuf) of Abraham. The red (ahmar) jafr is a leather bag which contains the weapons of the Prophet. Both types of jafr have been successively passed on to the 12th Imam. The Kitab al-Jafr contained remarkable statements concerning the interpretation of the Qur’an and concerning its inner meaning. (The statements in it) were transmitted on the authority of Jafar as-Sadiq